2D Heterojunction Between Double Perovskite Oxide Nanosheet and Layered Double Hydroxide to Promote Rechargeable Zinc‐Air Battery Performance. Issue 24 (22nd December 2020) - Mondal, Surajit; Majee, Rahul; Arif Islam, Quazi; Bhattacharyya, Sayan
Abstract: The role of two‐dimensional (2D) materials in electrocatalytic energy conversion reactions is unprecedented among which the earth‐abundant metal oxide nanosheets (NSs) that could promote bifunctional electrocatalytic oxygen reduction and evolution reactions (ORR/OER) remain elusive. <20 nm thick double perovskite oxide, Pr0.5 Ba0.5 Mn1.8‐ x Nb x Co0.2 O6‐δ (PBMNC‐ x, x =0–0.3, δ=0.38–0.59) NSs having a lateral spread of ∼300 nm were designed with exsolved metallic Co and Co3 O4 nanoparticles (NPs) anchored to the NS surface. PBMNC‐0.1 NSs demonstrate the best ORR/OER bifunctional activity among all PBMNC‐ x samples with a bifunctionality index (BI) of 1.36 V, which is the combined OER and ORR overpotential (η) at 10 and−3 mA/cm 2 current density, respectively. To promote the OER performance, chemically attached 2D heterojunctions of PBMNC‐0.1 NS and y mol % of NiFe (3 : 1) layered double hydroxide (NiFe‐LDH) were hydrothermally synthesized. Among the PBMNC/LDH‐ y heterojunctions, PBMNC/LDH‐20 shows the lowest BI of 1.06 V because of an electronic reorganization at the heterojunction as evidenced from Mott‐Schottky analysis. Proof of concept rechargeable zinc‐air battery (r‐ZAB) with PBMNC/LDH‐20 cathode exhibits a specific capacity of 695.6 mA.h/gZn and roundtrip charge‐discharge stability for 100 h at 5 mA/cm 2, surpassing the performance of state‐of‐the‐art Pt/C‐RuO2 couple. Abstract : Twice the fun : Spatially connected double perovskite oxide nanosheet and NiFe‐LDH reorganize the electronic environment, boosting bifunctional oxygen electrocatalysis at the cathode of rechargeable zinc‐air batteries.